Eksistensi Hak Budget DPR dalam Sistem Ketatanegaraan Indonesia - Susanto, Mei (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2016)
Eksistensi hak budget Dewan Perwakilan Rakyat (DPR) dalam sistem ketatanegaraan Indonesia pada saat ini setidaknya menimbulkan dua persoalan. Pertama, mengenai keberadaan hak budget DPR, khususnya setelah dihapuskannya Penjelasan UUD Tahun 1945. Kedua, persoalan mengenai urgensi keterlibatan DPR dalam pembahasan Rancangan Anggaran Pendapatan dan Belanja Negara (RAPBN) yang didalamnya muncul perdebatan mengenai sejauh mana keterlibatan DPR dalam pembahasan RAPBN tersebut. Pada praktiknya pun terjadi penyalahgunaan hak budget oleh oknum anggota DPR. Akibatnya muncul keinginan mengevaluasi hak budget DPR tersebut. Melalui Putusan No. 35/PUU-XI/2013, Mahkamah Konstitusi telah memangkas keterlibatan DPR dalam pembahasan RAPBN yang mendetil dari satuan unit organisasi, fungsi, program, kegiatan, dan jenis belanja menjadi hanya sampai unit organisasi, fungsi, dan program saja. Putusan Mahkamah Konstitusi tersebut dianggap telah mereposisi hak budget DPR. Namun, dalam praktiknya masih terjadi korupsi anggaran yang dilakukan oknum anggota DPR.The Existence of the Right of Budget of the House of Representatives in the Constitutional System in IndonesiaAbstractThe existence of the rights of budget of the House of Representatives in the Constitutional System in Indonesia at this moment at least raises two issues. First, regarding the existence of the right of budget of the House of Representatives in particular after the removal of Explanation of the Constitution of 1945. Second, the question of the urgency of the House of Representatives involvement in the discussion of the Draft State Budget (draft budget) in which there is a debate about the extent of the involvement of House of Representatives in the discussion of the draft budget. In practice, there is misuse of right of budget by unscrupulous members of the House of Representatives. Through Decision No. 35/PUU-XI/2013, the Constitutional Court has slashed the involvement of Parliament in the discussion of the detailed draft budget of the unit of the organization, function, programs, activities, and types of expenditure being only to organizational units, functions, and programs only. The Constitutional Courtâs decision is deemed to have rights to reposition the House budget. However, in practice budget corruption committed by individual members of Parliament still occurs.Â DOI: https://doi.org/10.22304/pjih.v3n1.a4